Notwendigkeit einer Finanzreform - Stefan Homburg (Wirtschaftsdienst, 1996)
Der Artikel befürwortet eine Reform des deutschen Finanzausgleichs. – – The article argues in favour of a reform of German intergovernmental fiscal relations.
Keywords: H77; 330; Intergovernmental fiscal relations; Finanzausgleich